(untitled) (diségno, 2026)
From September 11 to 13, 2025, the 46th International Conference of Representation Disciplines Teachers, organized by the Unione Italiana per il Disegno (UID), took place in Rome at Sapienza Università di Roma and Roma Tre University. The event was coordinated in close collaboration by faculty members from the Representation departments of the two universities, as well as from the telematic Università San Raffaele Roma, and was held under the patronage of the Institute for Advanced Studies on Heritage. [read more]